2007
DOI: 10.1523/jneurosci.4406-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of GABA within Adult Modulatory Systems Alters Electrical Coupling and Allows Expression of an Embryonic-Like Network

Abstract: The maturation and operation of neural networks are known to depend on modulatory neurons. However, whether similar mechanisms may control both adult and developmental plasticity remains poorly investigated. To examine this issue, we have used the lobster stomatogastric nervous system (STNS) to investigate the ontogeny and role of GABAergic modulatory neurons projecting to small pattern generating networks. Using immunocytochemistry, we found that modulatory input neurons to the stomatogastric ganglion (STG) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
(63 reference statements)
1
13
1
Order By: Relevance
“…This is consistent with either a developmental decrease in electrical coupling, or a consequence of the need to inject much more dye into the significantly larger adult neurons for it to travel into other neurons (Rehm, ). Nonetheless, it has been argued that changes in electrical coupling early in development are critical for the maturation of adult motor patterns (Ducret et al, ; Ducret et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with either a developmental decrease in electrical coupling, or a consequence of the need to inject much more dye into the significantly larger adult neurons for it to travel into other neurons (Rehm, ). Nonetheless, it has been argued that changes in electrical coupling early in development are critical for the maturation of adult motor patterns (Ducret et al, ; Ducret et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, these differences could be due to the immaturity of the neuromodulatory inputs (Fénelon et al, 1999; Kilman et al, 1999; Ducret et al, 2007; Cape et al, 2008), or developmental differences in the responses of STG neurons to neuromodulators. Therefore, we asked if Val 1 -SIFamide, a peptide that can modulate STG neurons in the adult lobster {Christie, 2006 #246}, was found in the same places in the neuromodulatory inputs of adults and embryos.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work had shown that the isolated embryonic STG responds to dopamine (DA), crustacean cardioactive peptide (CCAP), gamma-aminobutyric acid (GABA), and histamine (HA) (Richards and Marder, 2000; Pulver et al, 2003; Ducret et al, 2007) (Table 1). Although we did not do a detailed comparison with adult preparations, we tested for the presence of receptors for proctolin and allatostatin type A 3 (A-AST-3), modulators that are both present in the late embryonic STG inputs, and 5-HT, which first appears in the STG inputs during mid-late larval stages (Fénelon et al, 1999; Kilman et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations